Student’s Performance and Parent’s Involvement in Distance Learning: A Correlational Study - Marañon, Mar Joseph S.; Alegria , Jolises S.; Alfonso, Ranica M.; Cabatas, Lorebelle A.; Cruz, Kristine Joy A. De la; Peña, Queenilyn B. De la; Deocampo, Ray Andrew M.; Embino, Placido G.; Espellogo, Jeremeah T.; Grande, Jebalyn T.; Hinoguin, Lore Jean T.; Intig, Alexandra Marie R.; Mancia, Stephanie C.; Martesano, Philip Anthony P.; Nalaunan, Franz Ann P.; Reverial, Joseph Hanz S.; Villanueva, Jenika P.; Bacosa, Rogie P.; Castañeda, Denelle M.; Peacita, Simple Joy M.; Rollo, Iril Ian B.; Patrata, Anthony G. (Future Science / FSH-PH Publications, 2021)
Distance Learning had evolve through many ages and generation. This became the main source of teaching on the present since its become convenient and efficient to everyone. As COVID-19 pandemic creates a devastating effect throughout the world, Philippines become innovative on how they will able to adapt and continue the classes with the use of parents as the molder of their children. The main objective of the study is to correlate the level of parent’s involvement on students’ performance in distance learning of Negros Occidental High School during this times of pandemic. A sample size of three hundred thirty-six (336) students were accommodated in the study covered the Senior High School day class students for S.Y. 2020-2021 who are under the two learning modalities — print and digital learning and were randomly selected from different strands both Academic and Non Academic Tracks composed of grade levels namely Grade 11 and 12. A researcher made survey questionnaire was used as a research instrument to gathered data. Proper encryption and verification of data was done to derive a certain result. Results shown that parents involvement in distance learning have no significant relationship towards the performance of the student. The proponents suggested continuing the wider scope of the same study with having larger samples in expanding the range to both Junior High School and Senior High School in order to show various results may add to the body of knowledge in parent’s involvement and student’s performance.